2021
DOI: 10.1186/s13048-021-00844-7
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted hatching in lower grade cleavage stage embryos improves blastocyst formation: results from a retrospective study

Abstract: Background Laser-assisted hatching (LAH) has been widely applied to facilitate blastocyst hatching in IVF-ET treatment, however, the effect of LAH on subsequent development and clinical outcomes of the lower grade cleavage stage embryos (LGCE) remains unknown. Our study aimed at evaluating the effect of LAH on blastocyst formation and the clinical pregnancy outcomes of LGCE embryos after transfer. Methods A total of 608 cycles of IVF/ICSI treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
2
10
1
Order By: Relevance
“…Our results showed that the LAT treatment have an equivalent value to LAO in terms of total, viable, top-quality and hatched blastocyst formation, as well as the clinical outcomes after blastocyst transfer. Both LAO and LAT have better blastulation outcomes compared to those of non-treated low-graded embryos, as reported in our previous study ( 3 ).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Our results showed that the LAT treatment have an equivalent value to LAO in terms of total, viable, top-quality and hatched blastocyst formation, as well as the clinical outcomes after blastocyst transfer. Both LAO and LAT have better blastulation outcomes compared to those of non-treated low-graded embryos, as reported in our previous study ( 3 ).…”
Section: Discussionsupporting
confidence: 85%
“…Finally, a total of 166 day-3 embryos developed into blastocyst stage (52.70%), of which 97 were viable blastocysts (30.79%), and 42 top-quality ones (13.33%). The blastulation outcomes here were obviously higher than those for untreated embryos as reported in our previous study (40.2%, 18.6% and 9.2%, respectively) under the same cultural conditions ( 3 ).…”
Section: Resultscontrasting
confidence: 78%
See 3 more Smart Citations